JLIS - Vol. 4 n.2 (2013) - aa. vv (Ledizioni, 2013)
JLIS, the Italian Journal of Library and Information Science, is an academic journal of international scope that aims to valorize the Italian research in the LIS field, and it welcomes contributions from young students and scholars. The journal board encourages authors (students, researchers, librarians, archivists) to contribute with interdisciplinary or innovative papers, hoping that they can use JLIS as a virtual space for theoretical elaboration on the radical transformations happening to cognitive processes of knowledge fruition, and to professional practices due to digital culture innovations. JLIS.it publishes one volume in two six-monthly issues, in June and December.